Optimization of an automatic irrigation system for precision irrigation of blueberries grown in sandy soil. (1st June 2017) - Egea, G.; Muñiz, J.; Diaz-Espejo, A.
Abstract : An experiment was carried out to assess the performance of an automatic irrigation system based on remotely-sensed soil moisture measurements in blueberries grown in sandy soil under plastic tunnels. The system uses the information provided by soil moisture sensors installed at three soil depths (10, 20 and 30 cm) and user-defined irrigation set-points to trigger automatic irrigation events. An Optimized irrigation treatment in which irrigation set-points and duration of irrigation have been determined from soil hydraulic properties analysis and soil water modelling is compared to the irrigation scheduling criteria established by the grower (Control treatment). The results showed that the Optimized treatment applied 30% of the water applied by the Control treatment, led to mild to moderate crop water stress conditions and had no impact on berry yield and quality.